Nutritional determinants & cardiometabolic risk outcomes in children and adolescents with obesity - Saner, Cristoph (fi=Turun yliopisto|en=University of Turku|, 2020)
Total energy intake, physical activity, body size and body composition determine total energy expenditure. An imbalance between total energy intake and total energy expenditure causes obesity. Overweight and obesity remains the most prevalent, modifiable cardiovascular risk factor for children and adolescents. In adolescence, obesity is associated with adverse non-invasive, subclinical cardiovascular phenotypes. In adulthood, these subclinical cardiovascular phenotypes and specific, obesity-related serum metabolomic profiles are predictive of future cardiovascular disease (including stroke and myocardial infarction) and cardiovascular disease mortality. To investigate the association between determinants for total energy expenditure with the severity of obesity, with obesity-related cardiometabolic risk factors and with subclinical cardiovascular phenotypes in children and adolescents with obesity. The present study was based on data from participants of the Childhood Overweight Biorepository of Australia (COBRA) and a derivative, longitudinal study-arm entitled COBRA-CVR (COBRA-Cardiovascular Risk). COBRA is comprised of 438 children and adolescents aged 6–18 years with overweight and obesity. COBRA-CVR includes a subset of 101 former COBRA-participants with obesity, aged up to 25 years, who were followed¬up an average of 5.5 years later for the COBRA-CVR sub-study. Among youth with obesity, low grip strength (a global measure of muscular strength) was associated with poorer cardiometabolic health indicated by higher systolic blood pressure, higher low-density lipoprotein-cholesterol, higher carotid intima-media thickness (cIMT) and higher continuous metabolic syndrome score. Compositional analysis of macronutrients revealed that the dietary proportion of proteins is negatively associated with total energy intake, irrespective of whether carbohydrates or fats were the diluents. Several adiposity measures (including body mass index, waist circumference, bioimpedance related percentage body fat) showed associations consistent in direction and strength with metabolites that are associated with cardiovascular disease risk. Particularly, adiposity-related metabolomic profiles in post-pubertal males resembled profiles from adults that are predictive for cardiovascular disease and mortality. Increasing the severity of obesity from early to late adolescence was associated with increased pulse wave velocity (PWV) in males and with reduced carotid elasticity in females. Moreover, blood pressure was positively associated with PWV and glycoprotein acetyls (GlycA, a measure of chronic inflammation) was negatively associated with carotid elasticity. Male sex was the only factor associated with increased cIMT. Obesity in youth is a multifactorial disease of pandemic scale that is in need of methods for prevention and risk stratification to alleviate the associated negative public health impacts. This study provides evidence for approaches that are clinically translatable to youth with overweight or obesity: to reduce total energy intake by ensuring sufficient protein intake; and factors that could help identify those at higher risk for adverse cardiometabolic outcomes.

Ravitsemuksen vaikutus lapsuuden ylipainon kehittymiseen ja sydänterveys vaikeasti ylipainoisilla lapsilla. Lihavuus johtuu energian saannin ja kulutuksen epätasapainosta. Se on lapsilla keskeinen sydän-ja verisuonitautien riskitekijä. Teini-ikäisillä lihavuus lisää varhaisten, oireettomien valtimomuutosten esiintyvyyttä. Aikuisilla nämä valtimomuutokset sekä lihavuuteen liittyvät metaboliset muutokset ennustavat sydän-ja verisuonitapahtumia ja niihin liittyvää kuolleisuutta. Väitöskirjatutkimuksen tavoitteena oli selvittää ravitsemuksen vaikutuksia lapsuusiän lihavuuden vaikeusasteeseen ja tutkia kehon koostumuksen yhteyttä veren metabolomiikkamuuttujiin sekä varhaisiin valtimomuutoksiin. Lisäksi tutkimuksessa arvioitiin käden puristusvoiman yhteyttä varhaisten valtimomuu¬tosten ilmenemiseen. Väitöskirjatutkimus on osa australialaista Childhood Overweight Biorepository of Australia (COBRA)-tutkimusta ja sen jatko-osaa COBRA-CVR. COBRA¬tutkimukseen osallistui 438 iältään 6–18-vuotiasta ylipainoista tai lihavaa lasta, joista 101 osallistui COBRA-CVR-jatkotutkimukseen. Ravintoainesanalyysin perusteella ravinnon proteiiniosuus oli sokeri-ja rasvakulutuksesta riippumatta tutkimusryhmässä käänteisesti yhteydessä kokonaisenergiansaantiin. Metabolomiikka-analyyseissä eri kehonkoostumusmittarit korreloivat useisiin metaboliitteihin, joiden on todettu ennustavan valtimotautiriskiä. Yhteydet olivat vahvimpia teini-ikäisillä pojilla. Lihavuuden vaikeutuminen teini-iässä oli yhteydessä varhaisiin valtimomuutoksiin, pojilla lisääntyneeseen valti¬moiden jäykkyyteen ja tytöillä alentuneeseen kaulavaltimon joustavuuteen. Lisäksi verenpaine korreloi suoraan valtimoiden jäykkyyteen ja inflammaatiotekijä glykoproteiini-A käänteisesti kaulavaltimon joustavuuteen. Alentunut käden puristusvoima oli yhteydessä korkeampiin systolisen verenpaineen, LDL-kolesterolin, kaulavaltimon seinämäpaksuuden ja metabolisen oireyhtymän riskipisteytyksen arvoihin. Ravintoainesanalyysi voi antaa lisätietoa painonhallintaan. Etenkin teini-ikäi¬sillä pojilla vaikea lihavuus on yhteydessä metabolisiin muutoksiin. Lihavuuden vaikeutumisen estäminen teini-iässä saattaisi vähentää varhaisten valtimomuutosten esiintymistä. Käden puristusvoimamittauksilla voi olla mahdollista arvioida lihavien lasten alttiutta valtimotaudin riskitekijöille.